Conceptual design of cantilever support for long haul bus passenger seat - Tan, CheeFai; Tean, Z.Y.; Said, M.R.; Khalil, S.N.; Sudin, M.N.; Karjanto, Juffrizal; Yusof, N.M.; Sivarao, Subramonian (2013)
This paper describes the conceptual design of cantilever support for long haul bus passenger seat. The advantages of cantilever bus seat structure is light weight, the luggage can be put under the seat and it is easy for floor cleanup. The total design technique was used to develop the cantilever support. Market survey was conducted to study on current available cantilever supported vehicle seat. After that, product requirement of cantilever design is defined. Next, brainstorming technique was used to generate the preliminary concept of cantilever design. Six conceptual designs were generated for selection. The matrix evaluation method was used to determine the final design of cantilever design. The weight of the concept was obtained through weighted analysis. Lastly, the final concept will be fabricated as prototype for further validation purpose.